Improving the usability of online resources to support implementation research and practice: The RE-AIM website use case - Pereira, Emiliane L.; Strayer, Thomas E.; Harden, Samantha M.; Glasgow, Russell E.; Studts, Christina; Estabrooks, Paul A.; Huebschmann, Amy G. (Journal of clinical and translational science, 2025)
Our overall goal was to enhance the usability and interactivity of the RE-AIM website (re-aim.org) and improve resources to support the application of the RE-AIM framework within the context of dissemination & implementation (D&I) research and practice. We applied a mixed-methods approach to obtain user feedback from 24 D&I researchers and practitioners. Usability (System Usability Scale) and interactivity (Interactivity Scale) were assessed through validated surveys, at baseline and after two iterative rounds of website modifications (Phase 1 and Phase 2). We also conducted qualitative assessments at each phase. Qualitative baseline and Phase 1 findings indicated a need to simplify organization, enhance information accessibility, provide concrete guidance on applying RE-AIM, and clarify contextual factors related to RE-AIM constructs. After streamlining website and homepage organization, Phase 2 qualitative results suggested improved user navigation experience; users also requested greater interactivity. Modifications included: new interactive planning tool and a video introduction of contextual factors influencing RE-AIM outcomes. Significant improvements were found in the SUS score from baseline to Phase 1(64.2[SD18.7] to 80.8 [SD 12.1] ( < .05) and remained higher in Phase 2(77.1[SD 15] ( = 0.08). Interactivity also improved from baseline to Phase 2(3.5[SD1.2] to 41[0.9], though not statistically significant. User-centered feedback on online resources, as exemplified by this use case example of enhancements to the RE-AIM website, are important in bridging the gap between research and practice, and the revised website should be more accessible and useful to users.